2023
DOI: 10.1177/14644193231154159
|View full text |Cite
|
Sign up to set email alerts
|

Study on nonlinear dynamic characteristics of power six-branch herringbone gear transmission system with 3D modification

Abstract: The power six-branch herringbone gear transmission system has the advantages of large power transmission and transmission ratio. Because of its multi-way transmission and over-constraint structure, to prevent loaded tooth interference, there are large backlashes between teeth. The system shows complex nonlinear dynamic characteristics under the influence of backlashes, which seriously affects meshing performance. The modification technology can effectively improve gear meshing performance. Hence, on the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Using the Runge-Kutta 33 method solving the dynamic equations (7)(8)(9)(10)(11)(12)(13)(14)(15), the dynamic meshing force of each gear pair is obtained, and they are shown in Supplementary Figures 8 and 9.…”
Section: Calculation Of Lscmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Runge-Kutta 33 method solving the dynamic equations (7)(8)(9)(10)(11)(12)(13)(14)(15), the dynamic meshing force of each gear pair is obtained, and they are shown in Supplementary Figures 8 and 9.…”
Section: Calculation Of Lscmentioning
confidence: 99%
“…The study found that the asymmetrical phenomena under different meshing states significantly affect the nonlinear characteristics of the system's rearside collision, especially in the parameter range from chaotic state to periodic state. Li et al [11][12][13] combined three-dimensional modifications with the system's nonlinear vibration characteristics and proposed an analysis method for the nonlinear vibration characteristics of the system under three-dimensional modifications. The study investigated the influence of different system parameters on the nonlinear dynamic characteristics of the system under three-dimensional modification and nonmodification.…”
Section: Introductionmentioning
confidence: 99%
“…As an important transmission component, herringbone gears are widely used in high-speed, heavy-duty, and high-power transmission systems such as aviation and vessel transmission equipment and other mechanical transmission areas because of their advantages in transmission stability and strong bearing capacity [4][5][6]. Therefore, high accuracy in the manufacture of herringbone gears is increasingly required [7][8][9][10]. Even more, the spatial symmetry of herringbone gears directly affects transmission errors, transmission efficiency and service life, which are significant for transmission systems [11,12].…”
Section: Introductionmentioning
confidence: 99%